The application of leaf anatomy identifying species of Orchidantha N.E.Br. (Lowiaceae Ridl.) in Malaysia - Yusoff, Nur; Kalu, Meekiong; Siam, Nordahlia (Reinwardtia, 2025)
YUSOFF, N. S. S. M., KALU, M., & SIAM, N. A. 2025. The application of leaf anatomy identifying species of Orchidantha N.E.Br. (Lowiaceae Ridl.) in Malaysia. Reinwardtia 24(1): 17‒25. — Lowiaceae only consists of one genus, Orchidantha, which with thirty-four species has the lowest number of species among the eight families within order Zingiberales. Recently, Orchidantha has garnered attention for its potential medicinal value in treating fever, cough, chest, and back pain. The species are often only found in a small area. The morphology of the flower of Orchidantha is essential to identification but often the flowers are rarely found. As a result, this study aims to investigate vegetative anatomical characteristics of the petiole, midrib, and lamina, which could be used for species identification independent of availability of flowers; by identifying shapes and special characteristic of labellum, stigma, and viscidium. The results of this study shown a marked difference in shape and depth of the petiole grooves, petiole margin, and the number of vascular systems. In conclusion, the study demonstrates that the anatomical‒petiole grooves, petiole margin and number of vascular systems, are useful for identifying species.